Impact of delayed processing of positive blood cultures on organism detection: a prospective multi-centre study - Roberts T. (2023)
Background: Blood cultures remain the gold standard investigation for the diagnosis of bloodstream infections. In many locations, quality-assured processing of positive blood cultures is not possible. One solution is to incubate blood cultures locally, and then transport bottles that flag positive to a central reference laboratory for organism identification and antimicrobial susceptibility testing. However, the impact of delay between the bottle flagging positive and subsequent sub-culture on the viability of the isolate has received little attention. Methods: This study evaluated the impact of delays to sub-culture (22 h to seven days) in three different temperature conditions (2–8 °C, 22–27 °C and 35 ± 2 °C) for bottles that had flagged positive in automated detection systems using a mixture of spiked and routine clinical specimens. Ninety spiked samples for five common bacterial causes of sepsis (Escherichia coli, Haemophilus influenzae, Staphylococcus aureus, Streptococcus agalactiae and Streptococcus pneumoniae) and 125 consecutive positive clinical blood cultures were evaluated at four laboratories located in Cambodia, Lao PDR and Thailand. In addition, the utility of transport swabs for preserving organism viability was investigated. Results: All organisms were recoverable from all sub-cultures in all temperature conditions with the exception of S. pneumoniae, which was less likely to be recoverable after longer delays (> 46–50 h), when stored in hotter temperatures (35 °C), and from BacT/ALERT when compared with BACTEC blood culture bottles. Storage of positive blood culture bottles in cooler temperatures (22–27 °C or below) and the use of Amies bacterial transport swabs helped preserve viability of S. pneumoniae. Conclusions: These results have practical implications for the optimal workflow for blood culture bottles that have flagged positive in automated detection systems located remotely from a central processing laboratory, particularly in tropical resource-constrained contexts.